L’intersoggettività e la sfera “emozionale-affettiva”. Appunti per una rilettura dell’analisi costitutiva - Muzzetto, Luigi (SocietàMutamentoPolitica, 2012)
In the first part of the essay are highlighted the assumption, in classical sociology, of emotion and rationality as opposing elements, and the presence of the fundamental aspects of the overcoming of such dichotomous view. The second part draws on Schutz’ thought on intersubjectivity as a social basic category. Although Schutz adopts a cognitive perspective, the essay underlines elements in his thought that allow to propose a new conceptualization in which the affective-emotional dimension is present ‘since the beginning’.